Prince citoyen ou monarque au-dessus des lois ? - Mathias Nicolleau (Cahiers Mondes Anciens)
At the end of the year 48 A.D., the emperor Claudius decided to marry his niece Agrippina. However, this marriage broke Roman traditional norms about incest. To not be considered as a tyrant satisfying his whims without any restraint and at the risk of endangering the city, Claudius maneuvered so that this marriage seemed to result from the unanimous will of the Senate and the People, and he obtained the vote of a decree authorizing such a union. Claudius thus conformed to the model of the ciuilis princeps respectful of traditional norms and institutions, which allowed him to have his pre-eminence within the res publica recognized by all, and so to legitimate his power. Indeed, such incestuous marriages were typical of foreign royal dynasties, which they helped to distinguish from the populations. Claudius thus got to be recognized himself as an extra-ordinary monarch, far above other citizens.